Efficacy and safety outcomes of sofosbuvir-based treatment regimens for hepatitis C virus-infected patients with or without cirrhosis from phase III clinical trials - Yang YM; Choi EJ (Dove Medical Press, 2017)
Young-Mo Yang, Eun Joo Choi Department of Pharmacy, College of Pharmacy, Chosun University, Gwangju, South Korea Background: With the appearance of oral direct-acting antivirals (DAAs), the field of hepatitis C virus (HCV) treatment has been dramatically changed. This evolution makes possible for all oral treatments to be available for the treatment of HCV-infected patients. The aims of this review were to report the efficacy and safety of sofosbuvir (SOF)-based regimens for the treatment of patients with chronic HCV infection and to provide our clinical perspectives on these regimens. Methods: A literature search of clinical studies published in PubMed and posted on ClinicalTrials.gov website was performed to identify studies evaluating the efficacy or safety of SOF-containing treatment regimens. Results: A total of 23 clinical trials were examined in the review. The evaluated SOF-based regimens are as follows: SOF/daclatasvir (DCV) ± ribavirin (RBV), SOF/ledipasvir (LDV) ± RBV, SOF/simeprevir (SMV), SOF/velpatasvir (VEL) ± RBV, and SOF/RBV ± peginterferon (peg-IFN). These SOF-based regimens were at least effective and safe for HCV-infected patients with or without cirrhosis. The SOF/VEL ± RBV regimen, a pan-genotypic DAA regimen, was effective for the treatment of patients with HCV genotype 1, 2, 3, 4, 5, or 6 infection. The 24-week SOF/RBV regimen was as effective as the 12-week SOF/RBV/peg-IFN regimen. Patients with HCV genotype 3 infection could have benefits from the use of the 24-week SOF/RBV regimen. For cirrhotic patients with HCV genotype 3 infection, the 12-week SOF/RBV/peg-IFN regimen could be considered as an alternative treatment option when access to SOF-based regimens with other DAAs is limited. In the included studies, significant adverse events due to SOF-based regimens were not reported. Conclusion: The clinical trials suggest that SOF-based treatment regimens for HCV-infected patients with or without cirrhosis can be at least effective and safe patient-convenient medications. However, it is necessary to monitor HCV-infected patients, since rare adverse events, drug–drug interactions, and drug–disease interactions can occur in real clinical settings. Keywords: hepatitis C, direct-acting antiviral, sofosbuvir, efficacy, safety, drug–drug interaction